2005
DOI: 10.1177/153476560501100405
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth Following the Terrorist Attacks of September 11, 2001: Cognitive, Coping, and Trauma Symptom Predictors in an Internet Convenience Sample.

Abstract: Cognitive, coping, and trauma symptom predictors of posttraumatic growth (PTG; measured with the Posttraumatic Growth Inventory) were examined in a large convenience sample (n =1505) participating in a longitudinal Internet-based study following the terrorist attacks of 9/11/01. Results indicate that initial PTG levels (mean 9 weeks post-attacks) were generally associated with higher trauma symptoms (measured with the PTSD Checklist - Specific), positive changes in worldview (measured with the Changes in Outlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(109 citation statements)
references
References 50 publications
(81 reference statements)
15
90
2
Order By: Relevance
“…Also among the employed predictors in this study it was indicated that cognitive assessment -as previous studies mentioned (30,31) -played the greatest role in predicting growth, in other words, being problem-oriented and re-evaluating the recurred cancer, in line with PTG's outcomes, help the patients to be more compatible with negative consequences of cancer (32), feeling more competency (12) and having better psychological performances (33) as well.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Also among the employed predictors in this study it was indicated that cognitive assessment -as previous studies mentioned (30,31) -played the greatest role in predicting growth, in other words, being problem-oriented and re-evaluating the recurred cancer, in line with PTG's outcomes, help the patients to be more compatible with negative consequences of cancer (32), feeling more competency (12) and having better psychological performances (33) as well.…”
Section: Discussionmentioning
confidence: 74%
“…The results of this study, about no significant correlation between emotion-focused coping and PTG, suggested more important role of problem-oriented coping compared with positive consequences. More than that, for explaning this finding about emotion-focused copings, we can consider hypothesis of Tedeschi and Calhoun (29) that in a period of time, the person involving with trauma will probably be more eager to emotionoriented strategies -such as denial and avoidance-to dealing with the situation and preventing being overwhelmed with intensive negative emotions brought about by the event in order to encounter to it later; however, over time, he/she attempts to find more cognitive analysis and benefits re-conceptualize the event (24,30). Our correlation result about emotion-oriented coping is not positive, although it will be helpful to consider the above mentioned hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation which might account for this discrepancy is the possibility of a curvilinear relationship between distress and growth. Recent studies have explored a curvilinear relationship between growth and PTSD symptoms and found the highest levels of growth were reported by those who endorsed moderate levels of PTSD symptoms (Butler et al, 2005;. It is thought that low levels of distress may not be sufficient to induce growth whereas overwhelming levels of distress may inhibit growth (McCaslin et al, 2009).…”
Section: Variables Associated With Growthmentioning
confidence: 99%
“…Other studies suggest a curvilinear relationship, i.e. an intermediate level of post-event distress being associated with the greatest level of growth (Butler et al, 2005;McCaslin et al, 2009). …”
Section: Relationships Between Post-event Distress and Growth Among Fmentioning
confidence: 99%